Myth and temporality - Zilberberg, Claude (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
The elementary structures of temporality obey the fundamental dissymmetry between accented magnitude (or tonic) and unaccented (or unstressed) magnitude in the plane of expression, between intensive magnitude and extensive magnitude in the plane of the content, and in a general way between intensity and "extensity". These elementary structures concern the three dimensions of figurality, namely, the tempo, duration and spatiality, that is, the constitutive elements of what Hjelmslev calls the "figures". From these two series of premises, it is possible to describe singular discursive morphologies. In the text presented, we have devoted ourselves to reminiscence in the first place, striving to show that the importance that some of the greatest writers have been granted is explained by formal properties that associate tempo, duration and spatiality. The second direction of this study is to approximate the discursive magnitudes of the affect and the event, to see in the affection a "subjective" variety, in the event an "objectual" variety, situating them as dependent on the supervening, that is, , of a structure dictated by a very lively tempo. In short, the myth, independently of the figurative contents that it affirms, it appears as an inverted morphology of reminiscence and as a chronopoiesis in search of a compromise, of a plausible mediation between the sudden disrupter of supervening and the calming slowness of becoming. By doing so, the subject becomes, or becomes again, according to a beautiful expression of P. Ricoeur, the "guardian of time".